Greening Construction : The Role of Carbon Pricing - Carbon Pricing Leadership Coalition; International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
This report examines how to design effective carbon pricing mechanisms (CPMs) for the construction industry. As the world’s largest consumer of raw materials, it accounts for a significant proportion of final energy demand and is responsible for 25 percent to 40 percent of global carbon-related emissions. Demographic trends underline the need for the construction industry to do more to address its contribution to climate change. The world’s population is predicted to reach nearly 10 billion by 2050, with the majority expected to live in urban areas. This will increase demand for buildings and infrastructure; some estimates suggest that 75 percent of the infrastructure needed by 2050 must still be built.